Hercules [videorecording (Blu-Ray + DVD)] - Menken, Alan (Disney Blu-ray., 2014)
"Taken from the gods as a newborn and adopted on Earth, Hercules is just an awkward pillar of strength trying to fit in. What he wants most is to impress his father Zeus. When Hercules discovers Hades' sinister plot to take over Mount Olympus, he goes from zero to hero and, with the help of his pals Pegasus and Phil, discovers that real strength comes from the heart"--Container.